Acute pancreatitis secondary to the use of the anabolic steroid trenbolone acetate. (2nd January 2019) - Kumar, Vidhya; Issa, Danny; Smallfield, George; Bouhaidar, Doumit
Abstract: Background: The use of performance-enhancing drugs has increased dramatically in the last decade with high prevalence reported among the young athlete population. Many of these drugs contain anabolic steroids and may carry potential significant side effects and health risks. We report a case of anabolic steroid-induced acute pancreatitis (AP) that recurred after the reuse of the same drug by the patient, confirming the causative relationship. Case report: A 24 year-old male presented with severe epigastric pain. His past medical history was significant for two hospitalizations during the last year with AP. During his hospital admissions, extensive workup was performed ruling out the common and uncommon causes of AP. Upon further pressing, the patient admitted to a history of past and current anabolic steroid use for athletic performance enhancement. He began this use four years ago and most recently started using trenbolone acetate (TA). The correlation between the timing of the anabolic steroids administration and the attacks of AP, along with ruling out other causes, confirmed TA as the cause of pancreatitis. Discussion: The side effects associated with the use of these increasingly prevalent drugs are difficult to study in clinical trials due to the unethical nature of their consumption. In addition, these medications are difficult to study due to the varied usage cycles and patterns, unknown origin and source, as well as often high dose ingestion. Physicians and body builders need to be aware of the possible serious consequences of their use.